2008
DOI: 10.1007/s12011-008-8298-1
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Arsenic and Children’s Intelligence: A Meta-analysis

Abstract: This present study was undertaken to investigate whether arsenic exposure increases the risk of children's low intelligence quotient (IQ) in China. MEDLINE, SCI, CNKI, and CBM search were organized for all documents published, in English and Chinese, between 1988 and 2008 using the following keywords: arsenic, intelligence, and IQ. As a result, four cross-sectional studies that assessed the development of low IQ in children who had been exposed to arsenic earlier in their life were included in this study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Additionally, control cases used for epidemiological work are typically from more affluent areas without arsenic exposure. In China, cross-sectional analyses have shown that children who live in rural areas have lower IQ scores than children who live in urban areas [18, 21, 36]. Children residing in poor rural areas are more often exposed to arsenic, which may exaggerate the inverse associations found between arsenic in drinking water and IQ scores [37].…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Additionally, control cases used for epidemiological work are typically from more affluent areas without arsenic exposure. In China, cross-sectional analyses have shown that children who live in rural areas have lower IQ scores than children who live in urban areas [18, 21, 36]. Children residing in poor rural areas are more often exposed to arsenic, which may exaggerate the inverse associations found between arsenic in drinking water and IQ scores [37].…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…For some risk factors, such as fetal alcohol syndrome/alcohol-related neurodevelopmental disabilities and environ mental tobacco smoke, a published meta-analysis could not be found.. For other risk factors, the available meta-analyses involved ecologic comparisons not suitable for calculating FSIQ loss. For fluorosis (Tang et al 2008) and arsenicosis (Dong and Su 2009), for example, meta-analyses reported only the mean FSIQ deficits of children in areas with endemic disease compared with control areas.…”
Section: Limitationsmentioning
confidence: 99%
“…This could be due to the aggregation of NaAs with HH, which could delay its metabolism and excretion as compared to NaAs in water that can be readily cleared by the kidneys. The fact that NaAs crosses the blood-brain barrier as well as the placental barrier freely (Dong and Su, 2009;Kang et al, 2007; Samanta et al, 2007), the NaAs-HH complex could be retained longer in the brain as compared to NaAs and AsH 2 O, which are washed out of the brain easily by the efflux system of the brain (Kusuhara et al, 1998). This prolonged presence of AsHH in the cells probably induces the process of myristoylation and palmitoylation in the cellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Since children tend to eat or drink less of a variety of foods and beverages than adults do, ingestion of contaminated food, juice or infant formula made from arsenic-contaminated water may represent a significant source of exposure. There is some evidence that long-term exposure to inorganic arsenic in children may result in low IQ scores (Dong and Su, 2009;Kang et al, 2007;Rocha-Amador et al, 2007). There is also evidence that inhaled or ingested inorganic arsenic can injure pregnant women.…”
Section: Introductionmentioning
confidence: 99%